WEALTH MANAGEMENT AND THE PUBLIC A STUDY ON THE AWARENESS AND KNOWLEDGE ABOUT WEALTH MANAGEMENT IN THE COMMON MAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The major purpose of this research is to compile a list of the several methods of domestic financial administration that are utilized by Indian families. There are several strategies that may be utilized to effectively manage wealth; nevertheless, the level of success achieved by any given strategy is directly proportional to the nature of the money being managed. The secondary objective is to establish whether or not the average investor possesses the knowledge and comprehension necessary for effective asset management. The method of research that was utilized in this study is referred to as descriptive research, and the sampling strategy that was employed to choose the samples was a simple one. Primary data were collected from the two hundred persons who took part in the study. The participants all provided their own answers to the survey questions. In order to do the necessary testing and analysis on the data that was obtained, we made use of Percentage Analysis. Even while individuals participate in a variety of types of wealth management, the findings of the study indicate that their awareness and knowledge of market circumstances, opportunities, and their ability to take risks are considerably missing. As a consequence of this, many facets of people's financial life require major improvement in order to accomplish the goals of effective wealth management and control.